Do exporting firms benefit from retail internationalization? Evidence from France - Angela Cheptea; Charlotte Emlinger; Karine Latouche (Institut für Angewandte Wirtschaftsforschung (IAW), 2015)
We explore the link between globalization of the retail sector and the export activity of firms from their origin country. In a previous paper (Cheptea et al., 2015), we showed that exporting firms from countries with internationalized retail companies benefit more from this process than firms from other countries. Two mechanisms can explain this effect: a trade cost advantage for retailers' domestic suppliers, or a shift in foreign demand from which benefit all origin country firms. In this paper we question which of the two mechanisms dominates. For that, we test whether retailers' supplying firms benefit more from the overseas expansion of retailers than other origin country firms. We employ French firm-level data to evaluate the effect for the two types of firms. We identify retailers' suppliers as firms that sell their products under French retailers' brands or labels, i.e. French firms certified with the IFS standard. Our empirical objective is to estimate whether firms with IFS certification have better export performance on markets where French retailers operate. We find that certified French firms are more likely to export, and export larger volumes, than non-certified firms to markets where French retailers established outlets. We also show that when French retailers close down their activities in a market, IFS firms face a drop in exports to this market in the subsequent years. The results are robust to the use of different sets of firm- and country-specific fixed effects, are unaffected by possible selection and endogeneity biases, and the presence in export markets of other retailers. This difference in behavior for certified and non-certified exporting firms confirms the trade cost advantage of retailers' suppliers, which is lost when French retailers exit from the destination country.
Keywords: F12; F14; F23; 330; Multinational retailers; Firm-level exports; Private standards